PENEGAKAN HUKUM TERHADAP PENAMBANGAN PASIR LIAR (Studi Kasus di Sekitar Aliran Sungai Brantas Kecamatan Ngantru, Kabupaten Tulungagung) - Luqmana, Vendra Dwiky; Makhali, Imam (MIZAN, Jurnal Ilmu Hukum, 2024)
Unlicensed sand mining around the Brantas River, Ngantru District, Tulungagung Regency has both positive and negative impacts. The use of the environment has caused quite serious environmental damage. Based on the provisions of the UUPPLH, this act has violated the articles on environmental damage. The formulation of the research problems: 1) How is the impact of illegal sand mining on the ecosystem around the Brantas River, Ngantru District, Tulungagung Regency? 2) How is the law enforcement against illegal sand mining around the Brantas River, Ngantru District, Tulungagung Regency?. This research uses a qualitative type of research with a case study approach. The results of this research were: 1) Sand mining has a positive impact on improving the economic level of the surrounding community. Mining has been carried out since a period of a dozen years ago. This activity has absorbed hundreds of workers and increased the local economic turnover. 2) According to Lawrence M. Friedmen there are 3 (three) legal subsystems, if all three can run then the rule of law can work well. As a law enforcement parameter, it must have a clear and acceptable arrangement. Structurally, law enforcement officers should be more assertive in carrying out their duties and functions. The culture of the community in utilizing the environment is also not directly proportional to compliance with the law in accordance with the provisions of the UUPLH. Sand mining is carried out without regard to the impacts of environmental damage. Economic motives are one of the fundamental reasons for society in its compliance to enforce applicable laws.